(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Language constitutes a fundamental component of human cognition and social interaction, extending its influence far beyond communication. Contemporary interdisciplinary research increasingly demonstrates that words significantly affect psychological states and physiological processes, thereby shaping overall human health. This article investigates the impact of language on human health through psycholinguistic, neurobiological, and clinical perspectives. It explores how verbal stimuli influence brain function, emotional regulation, stress responses, immune activity, and psychosomatic health outcomes. Particular emphasis is placed on mechanisms such as emotional priming, neuroplasticity, placebo and nocebo effects, and internal self-directed speech. Additionally, the role of therapeutic language in clinical and healthcare settings is critically examined. The findings suggest that words function as biologically and psychologically active agents capable of promoting healing or contributing to disease. Recognizing the health-related power of language has profound implications for medicine, psychotherapy, education, and public health communication.